Factors Assosiated with Smoking Behavior in Male Students at SMK Negeri 2 Sungai Penuh in 2024 - Mella Agrillia; Puspita Sari; Vinna Rahayu Ningsih (PT FORMOSA CENDEKIA GLOBAL, 2024)
Smoking behavior has become a widespread health issue in almost all countries of the world. WHO states that tobacco use causes more than 8 million deaths each year, of which 7 million are active smokers and 1.2 million are victims of second-hand smoke. The increase in the number of active smokers in Indonesia, especially among teenagers, continues. According to Deputy Health Minister Dante Saksono, Indonesia currently ranks third in the number of active smokers in the world, after China and India. The total number of smokers worldwide reached 70.2 million people, or about 34.5 percent of the global population, which is 33.8% with the prevalence of youth smokers at 12.8%. This type of research is quantitative research with a cross sectional study design. The total population of this study was 708 respondents. The sample in this study was selected through proportional random sampling technique, namely 92 respondents. The dependent variable is smoking behavior and the independent variables are knowledge, attitude, parents, peers, and cigarette advertising. There is a relationship between attitude (p value = 0.000), peers (p value = 0.000) and cigarette advertising (p value = 0.000) with smoking behavior. There is no relationship between knowledge (p value = 0.549) and parents (p value = 0.049) with smoking behavior.